The role of cell cycle-related genes in the tumorigenesis of adrenal and thyroid neuroendocrine tumors - Ekaterina Filipovich; Ekaterina Gorodkova; Anastasia Shcherbakova; Walaa Asaad; Sergey Popov; Galina Melnichenko; Natalya Mokrysheva; Marina Utkina (Heliyon)
The molecular mechanisms underlying adrenal and thyroid neuroendocrine tumors, including their tumorigenesis, progression, and metastasis, involve unique pathways regulating cell cycle progression. To better understand these mechanisms and pathways, extensive in-depth research on cell cycle-related genes is necessary. This review aims to describe and interpret current single-cell RNA sequencing studies on neuroblastoma, medullary thyroid cancer, and pheochromocytoma tumors. Our review summarizes differentially expressed cell cycle-related genes with distinct functions, highlighting their potential as therapeutic targets and components of panels used to determine tumor type or aggressiveness. Although some insights have been gained, there is still limited information on these topics, and further research is required to explore the regulatory mechanisms of these tumors.